Avaliação da imunogenicidade de vacinas de DNA e de proteínas recombinantes do envelope dos vírus chikungunya e zika - Amaral, Marcelo Pires [UNIFESP] (2018)
Chikungunya (CHIKV) and Zika (ZIKV) viruses’ infection have rapidly enhanced worldwide in the last decades. To date, there is no vaccine available or specific treatment against both viruses. The viral envelope proteins of CHIKV and ZIKV are the main immunodominant antigens of the viruses and have a crucial role during the infection in host cells. Furthermore, E2CHIKV and EZIKV are the main target of neutralizing antibodies against the respective viruses. In this work, we designed and optimized synthetic genes encoding E2CHIKV and EZIKV proteins, subcloned into pVAX1 vector to obtain the DNA vaccines (pVAX-E2CHIKV and pVAX-EZIKV) and purified using Endofree Plasmid Giga kit (Qiagen). The recombinant proteins E2CHIKV and EZIKV were produced as inclusion bodies in BL21(DE3) and BL21(DE3)RIL (respectively), then purified by affinity chromatography. The immunization strategies were performed with the homologous/heterologous prime-boost regimen, 15 days apart, with 100 μg (100 μL final volume) of the DNA vaccines (i.m.) pVAX-E2CHIKV or pVAX-EZIKV or with 10 μg (200 μL final volume) of the recombinant proteins (s.c.) E2CHIKV or EZIKV in the presence of different adjuvants (50 μg poly IC, 20 μg imiquimod or 10 μg CpG) inoculated in 6-8 weeks old female mice, C57BL/6 mice for the vaccines against CHIKV and BALB/c mice for the vaccines against ZIKV. All mice were bled 14 days after each immunization to evaluate specific humoral response, and euthanized 15 days after the last dose to collect spleen and popliteal and inguinal lymph nodes to evaluate specific cellular response. All procedures were performed in accordance to the guidelines of the UNIFESP’s Ethics Committee and approved under protocol number 5759150416. Among all the adjuvants evaluated, poly IC was shown the best candidate to follow the recombinant proteins E2CHIKV and EZIKV vaccines, inducing greater magnitude of specific humoral and cellular responses. C57BL/6 mice immunized with the DNA vaccine pVAX-E2CHIKV in the homologous protocol were not able to induce specific humoral response, unlike the homologous recombinant protein (E2CHIKV + poly IC) and the heterologous (pVAXE2CHIKV / E2CHIKV + poly IC) vaccines that induced high specific antibody titers. Analysis of the cellular response showed that 2 doses of the homologous DNA vaccine pVAX-E2CHIKV was able to induce only interferon γ (IFN-γ) producing cells. The homologous E2CHIKV + poly IC vaccine was able to induce greater magnitude response of IFN-γ producing cells and IgG anti- E2CHIKV, as well as the frequency of germinal center (GC) B cells and T follicular helper (TFH). These cellular responses were also observed in mice immunized with the heterologous vaccine (pVAX-E2CHIKV / E2CHIKV + poly IC), but to a lesser extent. BALB/c mice immunized with the homologous DNA pVAX-EZIKV and the recombinant protein EZIKV + poly IC vaccines had the lowest and the highest magnitude of specific humoral response, respectively. Both heterologous vaccines (pVAX-EZIKV / EZIKV + poly IC, and vice-versa) had a medium magnitude of specific humoral response. Although all immunization groups elicited cellular response after the different immunization strategies, the homologous EZIKV + poly IC vaccine was able to induce higher magnitude of IFN-γ producing cells and IgG anti-EZIKV, higher frequency of GC B cells and TFH, proliferation and production of the intracellular cytokines TNF-α and IFN-γ by CD4+ T lymphocytes (LT). Overall, homologous recombinant protein E2CHIKV or EZIKV vaccines in the presence of the poly IC adjuvant were able to induce greater magnitude of humoral and cellular response, however heterologous vaccine strategy may be another option to induce a better quality and range of the immune response against intracellular pathogens.